Semantic Aspects of Linguistic Borrowings from the English Language in the Polish Sociolect of Information Technology - Weber, Marek (Respectus Philologicus, 2006)
The paper focuses on the analysis of semantic aspects of linguistic borrowings from English in the Polish sociolect of information technology. After a brief discussion of the processes of computerisation of everyday life and the creation of information society, the article presents a definition of the Polish sociolect of information technology. The main categories of loanwords from the English language - quotes, loanwords proper, and semantic borrowings - are elaborated upon. History of research done by Polish linguists on the semantics of linguistic borrowings from English is summarized. An analysis of semantic changes of loanwords proper in the recipient language is conducted. Processes on the level of semantics pertaining to the category of semantic loans are explained. Major semantic fields within the sociolect are distinguished. Examples of semantic loans: klient (client), winus (windows), adres (address), klucz (key) are analyzed in order to illustrate identified semantic processes. It is pointed out that some computer terms are taken over by the general language as a result of the process of "emancipation of scientific and technical terminology." Attention is drawn to the fact that a significant number of specialized vocabulary has the status of internationalisms.